STRATEGI KERAJAAN BATAK (TAMIANG) MENGHADAPI SERANGAN KESULTANAN ACEH DI ABAD KE-16 M - Ery Soedewo (Balai Arkeologi Sumatera Utara, 2019)
The Batak reign was one of the countries mentioned by Portuguese written sources from the 16th century AD, once existing on the island of Sumatra. In the middle of the 16th century the sovereignty of the Batak Kingdom was threatened by the aggression of the Sultanate of Aceh to its neighboring countries on the island of Sumatra. Through a historical study of the main data in the form of two Portuguese records, Tome Pires and Ferna-O Mendes D. Pinto, it was revealed the potential strengths and strategies adopted by the Batak Kingdom in the face of the Aceh Sultanate's attack. The absence of fortifications as an element of state power, made the Batak Kingdom change its defense strategy from defensive to aggressive. The initiative of the attack carried out by the Batak forces was inseparable from the support of their allied countries. Although the alliance has been formed by the Kingdom of Batak with a number of countries, the glory belongs to the Sultanate of Aceh.